Factors that influence the use of the Internet for job-seeking purposes amongst a sample of final-year students in the Eastern Cape province of South Africa - Juliet R. Chiwara; Willie T. Chinyamurindi; Themba Q. Mjoli (SA Journal of Human Resource Management, 2017)
Orientation: Organisations are turning to the Internet in search for talent. A constituency often targeted are those students nearing the end of their tenure of study who are making a transition into the working world. Given this, it is important to understand not only those factors that influence the use of the Internet within the Human Resources (HR) talent search process, but also how such factors relate to actual intent to apply for jobs.